QUALITY OF EDUCATIONAL PROVISION IN FAST TRACK RESETTLEMENT SCHOOLS IN ZIMBABWE: A CASE STUDY OF CHIWODZA PRIMARY SCHOOL - Mavhunga, Pharaoh Joseph; Mazodze, Crispen (European Scientific Journal, ESJ, 2014)
This study sought to establish the quality of educational provision in primary schools in newly resettled farms in Zimbabwe through the Fast Track land reform programme that commenced in 2000. The schools, meant to service children of the newly resettled farmers, were hastily set up without much planning, thereby raising concerns on the quality of educational provision. The research adopted a case study design in which Chiwodza School was selected as a single case for deep probing. Data were collected using ethnographic techniques such as observation, document analysis and interviews with staff at the school. An analysis and interpretation of data established that there was a plethora of problems that affected the teaching and learning process in schools in newly resettled farms in Zimbabwe, thereby affecting negatively the quality of educational provision. Prominent among these problems were poor infrastructure, shortage of instructional materials, inadequate support from the Responsible Authority and School Development Committees, lack of staff development for teachers and school heads, and a general negative attitude of parents towards assisting the schools. The study recommends, inter-alia, urgent government subvention in the provision of classrooms, teachers’ accommodation and ablutions, while parents and the responsible authority, on the other hand, should assist with the provision of instructional materials.